Sosialisasi Budidaya Jagung Manis di Desa Tanah Merah, Kabupaten Kampar - Putri Lukmanasari; Kamar Zaman; Fitri Hardianti; Ernita Ernita; Sulhaswardi Sulhaswardi; Siti Yuli Meilanda Sormin (Karawo : Journal of Community Service (KJCS), 2026)
This community service activity aims to improve the knowledge and skills of the community, particularly women in the Family Welfare Movement (PKK), in sweet corn cultivation as an effort to optimize the use of yard land and strengthen household food security. The activity was conducted in Tanah Merah Village, Siak Hulu District, Kampar Regency, using a participatory approach. The methods used included outreach, technical cultivation training, interactive discussions, and ongoing mentoring. The material provided covered selecting superior seeds, planting techniques, fertilization, pest and disease control, and harvesting and post-harvest stages. The results of the activity demonstrated an increase in participants' understanding and skills in applying proper sweet corn cultivation techniques. Furthermore, there was a shift in community attitudes, leading to greater awareness of the importance of productive and sustainable yard land use. This activity also encouraged the emergence of small-scale, home-based agricultural initiatives with the potential to increase family income. Thus, this program not only contributes to community capacity building but also supports food independence and sustainable economic well-being at the local level.